The miR‐137 schizophrenia susceptibility variant rs1625579 does not predict variability in brain volume in a sample of schizophrenic patients and healthy individuals. Issue 6 (5th July 2014) - Rose, Emma J.; Morris, Derek W.; Fahey, Ciara; Cannon, Dara; McDonald, Colm; Scanlon, Cathy; Kelly, Sinead; Gill, Michael; Corvin, Aiden; Donohoe, Gary
Abstract The micro RNA 137 (miR‐137) variant rs1625579 has been identified as a genome‐wide significant risk variant for schizophrenia. miR‐137 has an established role in neurodevelopment and may mediate cognitive dysfunction in schizophrenia. This role of miR‐137 may be related to changes in brain morphology for risk‐related genotypes; however this has not yet been delineated. Here we considered whether rs1625579 genotype was predictive of indices of brain structure in patients with schizophrenia and healthy controls. Structural magnetic resonance imaging (sMRI) data (i.e. 3T T1‐TFE or 1.5T T1‐MPRAGE) were acquired from 150 healthy controls and 163 schizophrenic patients. Two volumetric analyses that considered the impact of miR‐137/rs1625579 genotype were carried out on sMRI data. In the first analysis, voxel based morphometry was employed to consider genotype‐related variability in local grey and white matter across the entire brain volume. Our secondary analysis utilized the FIRST protocol in FSL to consider the volume of subcortical structures (i.e. bilateral accumbens, amygdala, caudate, hippocampus, pallidum, putamen and thalamus). Several brain regions in both analyses demonstrated the expected main effect of participant group (i.e. schizophrenics < controls), yet there were no regions where we observed an impact of rs1635579 genotype on brain volume. Our analyses suggest that the mechanism by which miR‐137 confers risk for schizophrenia and impacts upon cognitive function may not be mediated by changes in local brain volume. However, it remains to be determined whether or not alternative measures of brain structure are related to these functions of miR‐137. © 2014 Wiley Periodicals, Inc.